2022
DOI: 10.1038/s41598-022-20334-0
|View full text |Cite
|
Sign up to set email alerts
|

RhoA and vigilin are candidates for immunohistochemical markers for epithelioid malignant mesothelioma

Abstract: Diagnostic markers of malignant mesothelioma (MM) have been extensively investigated. Immunohistochemistry (IHC) markers, such as calretinin, have been used for pathologic diagnosis. However, more diagnostic markers are required to improve the specificity and sensitivity of pathologic diagnosis. This study proposed two proteins as diagnostic markers for epithelioid MM. One is RhoA, an MM mutation-susceptible locus-derived protein, and another is vigilin, a lung small cell carcinoma marker. IHC was performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Protein distribution and location information in pathological samples are expected to be useful biomarkers by correlating them with histopathological findings associated with clinical findings. We have previously reported its use in colon cancer [1], acute myocardial infarction [2][3][4][5], glioblastoma and metastatic lung cancer [6], systemic lupus erythematosus (SLE) and its associated diseases [7][8][9], and malignant mesothelioma [10]. FFPE-based proteomics is a promising method for identifying disease biomarkers.…”
Section: Formalin-fixed Paraffin-embedded (Ffpe) Proteomicsmentioning
confidence: 99%
“…Protein distribution and location information in pathological samples are expected to be useful biomarkers by correlating them with histopathological findings associated with clinical findings. We have previously reported its use in colon cancer [1], acute myocardial infarction [2][3][4][5], glioblastoma and metastatic lung cancer [6], systemic lupus erythematosus (SLE) and its associated diseases [7][8][9], and malignant mesothelioma [10]. FFPE-based proteomics is a promising method for identifying disease biomarkers.…”
Section: Formalin-fixed Paraffin-embedded (Ffpe) Proteomicsmentioning
confidence: 99%
“…Changes in the amount for HDLBP could be identified in malignant mesothelioma (MM). The classification of MM is problematic since it is challenging to differentiate it from LAC (lung adenocarcinoma), ovarian cancer, or pleurisy, to just name a few examples [ 55 ]. To distinguish between MM types, an immunohistochemistry assay for the presence of HDLBP was performed.…”
Section: Hdlbp In Cancermentioning
confidence: 99%
“…It could be shown that epithelioid, sarcomatoid and biphasic MM, as well as LAC (lung adenocarcinoma) and LSC (lung squamous cell carcinoma) showed different abundance of HDLBP, indicating different expression levels of this protein. Therefore, in immunostaining diagnostics HDLBP has potential to be used for the differentiation between MM and LAC [ 55 ]. Taken together, HDLBP is clearly linked to cancer progression.…”
Section: Hdlbp In Cancermentioning
confidence: 99%